Somatotype differences between Mapuche and non-Mapuche children of 12 - 13 years old from Malleco - Araucania - Chile.: Diferencias del somatotipo entre niños mapuche y no mapuche de 12 - 13 años de Malleco – Araucanía – Chile. - Bruneau-Chávez, José (2020)
Somatotypic studies and their description of the human morphological configuration allow to appreciate impacts on eating habits and sedentary lifestyle. This study determined the somatotypic difference in Mapuche (NM) and non-Mapuche (NNM) children from Malleco, Chile. Through the ISAK protocol, 160 children with a mean age of 12.5 years, height 145.5 ± 3.5 cm and weight 43.7 ± 3 kg were evaluated, obtaining the following classifications: Group 12 years, Mapuche; mesoendomorphs. Non-Mapuche group 12 years; Endomesomorph. Group 13 years old, Mapuche; Mesoendomorphs. Non Mapuche group 13 years old; endomesomorph. The results indicate that for the age of 12 years, the NM presented lower values of endomorphy and higher values of mesomorphy (p≤0.01) than NNM. The 13-year-old NMs presented lower endomorphy and mesomorphy values (p≤0.01) than NNM. In conclusion, Mapuche schoolchildren present a mesomorphic predominance, however, NNM present a predominance of the endomorphic component.